USE OF HEPARIN GRAFTED DIALYZER (EVODIAL) FOR HEMODIALYSIS IN PATIENTS WITH HIGH RISK OF BLEEDING: A SINGLE CENTER EXPERIENCE - Pushevski, Vladimir; Shterjova Markovska, Zhaklina; Usprcov, Julijana; Gjorgjievski, Nikola; Trajcheska, Lada; Milenkova, Mimoza; Rambabova Bushljetic, Irena (Oxford University Press (OUP), 2023)
Background and Aims During hemodialysis exposure of the blood to the dialysis membrane and the tubing system can activate blood cells and promote clotting activation. So usually, some form of anticoagulation, most frequently heparin, is used to prevent blood coagulation. However, there are patients with increased risk for bleeding (patients with active bleeding, major surgery in past 72 hours, severe trombocytopenia) where use of heparin free regime is mandatory. Evodial dialyzer (Gambro-Hospal, France) [1] contains a heparin-grafted membrane aiming to provide a system with a low thrombogenicity that can be used without or with low dose heparin in order to reduce the patients' bleeding risk. As high-quality evidence of the optimal choice of anticoagulation in these patients is limited we wanted to show our experience with the use of Evodial dialyzer. Method During 12 months 106 dialysis sessions in 59 patients were performed. Reasons for using Evodial : active bleeding, hematological conditions, complications of vascular access. Changes in the dialyzer or the blood lines, or any aditional interventions were examined. Results Low dose unfractionated heparin (1250 IE total) was used in 10 (9,4%) sessions, and it was added in 15 (14%) more sessions because of problems with the coagulation. In 4 (2,8%) sessions we had to terminate dialysis because of clotting. Conclusion Heparin grafted dialyzers can be safely used in patients with high risk for bleeding. Although results are worse than the ones reported in literature [2] where regional citrate anticoagulation (RCA) is used, it can be reasonable alternative when RCA is unavailable.